Medicinal Plants in the Khok Pho District, Pattani Province (Thailand) - Wongsatit Chuakul (2017)
A survey on utilization of medicinal plants by herbalists in Khok Pho District, Pattani Province, Thailand was carried out by interviewing herbalists, collecting and identifying the plant specimens, and also comparing the plant specimens with the authentic specimens at two herbaria, i.e. at the Bangkok Herbarium, Botany Section, Botany and Weed Science Division, Department of Agriculture, Ministry of Agriculture and Cooperatives and at the Forest Herbarium, National Park, Wildlife and Plant Conservation Department. Ninety-five medicinal plants belonging to fifty-seven families commonly used as medicinal plants are reported. Of these ninety-five species, fourteen species are newly recorded as medicinal plants. Thirty-nine species are used in combinations with other medicinal plants in a total of sixteen different preparations.